2015
DOI: 10.1097/mat.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Release of Uremic Retention Solutes from Protein Binding by Hypertonic Predilution Hemodiafiltration

Abstract: Protein-bound uremic retention solutes accumulate in patients suffering from chronic kidney disease, and the removal of these solutes by hemodialysis is hampered. Therefore, we developed a dialysis technique where the protein-bound uremic retention solutes are removed more efficiently under high ionic strength. Protein-bound uremic solutes such as phenylacetic acid, indoxyl sulfate, and p-cresyl sulfate were combined with plasma in the presence of increased ionic strength. The protein integrity of proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 22 publications
0
44
0
3
Order By: Relevance
“…However, Böhringer et al have recently demonstrated in an in vitro study that the fraction of uremic toxins was signi-cantly decreased through hypertonic predilution hemodial-tration. 16 This nding underscores clearly the importance of ionic strength for the binding of toxins to HSA.…”
Section: -21mentioning
confidence: 99%
See 4 more Smart Citations
“…However, Böhringer et al have recently demonstrated in an in vitro study that the fraction of uremic toxins was signi-cantly decreased through hypertonic predilution hemodial-tration. 16 This nding underscores clearly the importance of ionic strength for the binding of toxins to HSA.…”
Section: -21mentioning
confidence: 99%
“…The importance of this toxin derives from the fact that quantitative experiments using equilibrium dialysis (ED) and chromatographic methods have revealed a considerable amount of PhAA present in dialysis patients prior and aer dialysis. 6,14,16 Furthermore, in a high performance liquid chromatography experiment (HPLC), it has been shown that PhAA accumulation in CKD patients inhibits the expression of inducible nitric oxide synthase and therefore might contribute to the higher cardiovascular risk of these patients. 2 The importance of ionic contributions to the binding of this toxin is demonstrated in an in vitro study by Böhringer et al and forms the basis for establishing a more effective clearance of PhAA by raising the ionic strength.…”
Section: -21mentioning
confidence: 99%
See 3 more Smart Citations